The therapeutic effect of secretome from human umbilical cord-derived mesenchymal stem cells in age-related osteoporosis. Issue 1 (4th December 2019) - Liang, Min; Liu, Wanguo; Peng, Zhibin; Lv, Shihong; Guan, Ying; An, Gang; Zhang, Yubo; Huang, Tianwen; Wang, Yansong
Abstract: Senile osteoporosis is closely related to the loss of function of stem cells. In this study, we tried to investigate the potential of secretome from human umbilical cord-derived mesenchymal stem cells (hUCMSCs) in recovering stem cell ability from senescence and then delaying bone loss. We first harvested bone marrow-derived mesenchymal stem cells (BMSCs) from young and old rats and then compared their cellular characteristics such as cell growth, anti-senescence and differentiation. The results showed that these abilities were negatively affected by animal aging. Subsequently, aged BMSCs were exposed to secretome from hUCMSCs, and we found that this loss of cell potential can be modified by secretome treatment. Thereafter, the secretome was loaded into silk fibroin-based hydrogels and used for an in vivo animal study. The results showed that compared to the old untreated group, the bone formation capacity of aged rats was improved by local treatment of secretome-loaded silk fibroin hydrogels. In conclusion, these findings demonstrated that secretome from hUCMSCs has the capacity to recover stem cell potential and delay local bone loss in age-related osteoporosis, which could potentially be applied in osteoporosis therapy in the future.